EVALUASI PENERAPAN TRIASE ATS (AUSTRALIAN TRIAGE SCALE) MODIFIKASI TERHADAP PASIEN TRAUMADI IGD RSUD TIDAR MAGELANG - Desi Rahmawati; Al Afik; Cipto Wahyuning Utama (JURNAL KESEHATAN INDRA HUSADA, 2025)
Emergency conditions can occur anywhere, anytime, and can be experienced by anyone. The Aim: This study aims to evaluate the implementation of ATS triage in the ER in patients with trauma. Method: This study used a descriptive quantitative design with a cross-sectional approach. The population was 36 nurses. The sampling technique used was purposive sampling with a sample size of 36 nurses. Data collection was carried out by observation. Data analysis used descriptive analysis with the help of computerization. Results: As many as 63.9% respondents were aged 25-35 years, male, had a Diploma 3 education, had a work period of ≥ 6 years and all had attended training such as BT and CLS. The implementation of ATS Triage on service waiting time, vital signs, and ATS examinations in patients with trauma showed that each triage category was in accordance with the SOP. In the implementation of vital signs due to several conditions, blood pressure and pulse examinations, especially in fussy children aged <12 years who were sometimes missed and only respiration, respiratory rate, temperature, VAS pain response, and GCS were checked. Conclusion: The application of ATS to trauma patients based on service waiting time, vital signs, and the application of ATS examination showed appropriate results and all were carried out according to SOP.